New Frontiers for Entertainment Computing - Ciancarini, Paolo; Nakatsu, Ryohei; Rauterberg, Matthias; Roccetti, Marco; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of refereed international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Enhancing Artificial Intelligence in Games by Learning the Opponent$1 (Bs Playing Style -- Using Game Engines for Visualization in Scientific Applications -- An Interactive Visual Canon Platform -- Physical Emotion Induction and Its Use in Entertainment: Lessons Learned -- Networked Virtual Marionette Theater -- Entertainment Computing in the Orbit -- A Collaborative Science Learning Game Environment for Informal Science Education:DinoQuest Online -- Construction and Evaluation of a Robot Dance System -- Context-aware fun and games with Bluetooth -- Comic Layout for Automatic Comic Generation from Game Log -- Computing Inspiration: i.plot -- Analysis and Generation of Japanese Folktales Based on Vladimir Propp$1 (Bs Methodology.s
Keywords: Computer science; Computers; Application software; Personal computers; Computer engineering; Computer Science; Theory of Computation; Computer Engineering; Computer Applications; Personal Computing; Computer Appl. in Social and Behavioral Sciences; Electronic books